Comparison of outcomes between aortic root replacement and supra‐coronary interposition graft for type A aortic dissection: A retrospective case series. Issue 12 (2nd October 2022) - Hartley, Philip; Salmasi, M. Yousuf; Morosin, Marco; Mensah, Kwabena; Asimakopoulos, George
Abstract: Background: The decision to conserve or replace the native aortic valve following acute type‐A aortic dissection (ATAAD) is an area of cardiac surgery without standardized practice. This single‐center retrospective study analysed the long‐term performance of the native aortic valve and root following surgery for ATAAD. Methods: Between 2009 and 2018 all cases ATAAD treated at Royal Brompton and Harefield NHS Foundation Trust were analysed. Patients were divided into two groups: (a) ascending aorta (interposition) graft (AAG) without valve replacement and (b) nonvalve‐sparing aortic root replacement (ARR). Preoperative covariates were compared, as well as operative characteristics and postoperative complications. Long‐term survival and echocardiographic outcomes were analysed using regression analysis. Results: In total, 116 patients were included: 63 patients in the AAG group and 53 patients in the ARR group. In patients where the native aortic valve was conserved, nine developed severe aortic regurgitation and two patients developed dilation of the aortic root requiring subsequent replacement during the follow‐up period. Aortic regurgitation at presentation was not found to be associated with subsequent risk of developing severe aortic regurgitation or reintervention on the aortic valve. Overall mortality was observed to be significantly lower in patients undergoing AAG (17.5% vs. 41.5%, p  = .004). Conclusions: With careful patient selection, the native aortic root shows good long‐term durability both in terms of valve competence and stable root dimensions after surgery for ATAAD. This study supports the consideration of conservation of the aortic valve during emergency surgery for type‐A dissection, in the absence of a definitive indication for root replacement, including in cases where aortic regurgitation complicates the presentation.